PATTERNS AND OUTCOMES OF PEDIATRIC BURN INJURIES IN A TERTIARY HOSPITAL’s BURN UNIT - Lisanu Asefa; Metasebia Worku Abebe; Abraham Gebregziabher Negussie (Burns Open, 2024)
Introduction: Burn is skin and tissue damage caused by various agents such as fire, scalds, electricity, chemicals, or radiation injuries. Globally, burn injuries pose a substantial public health challenge, with a high risk of mortality and morbidity, accounting for over 310,000 annual deaths. Nearly 75 % of burns in young children result from scald burns and infants have the highest mortality rates. Factors such as large surface area of burn, inhalational injury, poverty, and the presence of sepsis contribute significantly to mortality and morbidity in burns. Objective: To assess the pattern of presentation of pediatric burn injuries and their management outcomes. Methods: A hospital-based retrospective cross-sectional study was conducted. Data were extracted from patient charts, cleaned, coded, checked for completeness, and entered into SPSS version 25 for analysis. Descriptive statistics and logistic regression were used for data analysis, and graphical presentations were utilized to present the result findings. Results: Among the 218 paediatric burn patients admitted to the Addis Ababa Burn, Emergency and Trauma Hospital’s burn unit, 71.1 % had sustained scald burns due to hot water splashes, while 20.2 % of the patients were admitted due to flame burns. Superficial partial thickness burns occurred in 53.6 % of the patients, with the upper extremity and trunk being the most commonly affected sites. Approximately 38.2 % of the patients developed acute complications, with sepsis of the wound focus being the most common. Chronic complications occurred in 30.7 % of patients, primarily in the form of post-burn contractures. A mortality rate of 3.2 % was observed during the admission period with 2.3 % of deaths occurring in children under 5 years and those with major burns. Conclusion & Recommendation: The primary causes of burns in the pediatric age group are predominantly preventable scalds. Children, especially when unsupervised at home, particularly in kitchens, demand meticulous attention and care to mitigate the risk of burn injuries.